2016
DOI: 10.3390/su8070608
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in Human Well-Being in the Urban Ganges Brahmaputra Meghna Delta

Abstract: Abstract:The recently endorsed Sustainable Development Goals (SDGs) agenda unanimously agrees on the need to focus on inclusive development, the importance of eradicating extreme poverty and managing often complex human well-being impacts of rapid urban growth. Sustainable and inclusive urbanisation will accelerate progress towards the SDGs and contribute to eradicating extreme poverty. In tropical delta regions, such as the Ganges Brahmaputra Meghna delta region, urban growth and resulting intra-urban inequal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…A negative value means the disproportionate concentration among the poor group while a positive value indicates the concentration exists among the rich group. 14,15 A zero concentration index value indicates that there is no socio-economic inequality.…”
Section: Data Source and Methodsmentioning
confidence: 99%
“…A negative value means the disproportionate concentration among the poor group while a positive value indicates the concentration exists among the rich group. 14,15 A zero concentration index value indicates that there is no socio-economic inequality.…”
Section: Data Source and Methodsmentioning
confidence: 99%
“…As a consequence, a widespread shift in land use practice, rural-urban migration and seeking employment in non-natural resource-dependent livelihood activities have been emerging [117,120,140]. However, it has also been observed that vulnerability has intensified as a consequence of widespread poverty, limited access to natural resources and insufficient institutional development at the local level [61,[141][142][143][144]. In relation to rural livelihoods, resource distribution and access are particularly important because ownership of resources enhances the capacity of affected communities to take adaptive actions [89].…”
Section: Case Study: Rural Livelihood Vulnerability In Bangladeshmentioning
confidence: 99%
“…The socio-economic properties of rural Bangladesh include poverty, disproportionate distributions of livelihood resources and socially-embedded political marginalization, generally maintained by insufficient and often inefficient institutional systems at local levels (see for detail Rahman et al, 2014Rahman et al, , 2015Haq and Ahmed, 2016;Szabo et al, 2016;Alam, 2017;Islam, 2017). In relation to rural livelihoods, resource distribution and access are considered particularly important because resource ownership enhances the capacity of affected communities to take adaptive actions (Ribot, 2014).…”
Section: Vulnerability Of Land Use-based Rural Livelihoods In Bangladeshmentioning
confidence: 99%